Policy Strategy for Resolving the Post Pandemi Covid-19 Economic Crisis in Sri Lanka - Wijaretne, Toshiwa (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study provides an overview of the condition of the declining economy faced by cleavage world with exists plague pandemic Covid-19 as well as shape policies taken by Sri Lanka in responding to the threat of the economic crisis in future. It can be concluded that the existence of the Covid-19 pandemic has had an impact which is quite large and influential throughout the world. A number of sector affected industry even went bankrupt. With there policies taken by some countries to disconnect the spread of this virus is like barring out entry of foreign nationals into a country, self-quarantine or regional quarantine or restrictions on individual activities that have various impacts sector like sector tourism, economy etc. Individual activity restrictions and the economy has an impact for sectors such as decreased income, decreased purchasing power up to massive increase in layoffs and rising unemployment. This condition if no handled with good and serious in period long worried could raises the threat of a prolonged economic crisis, this will disrupt stability country. Policy fiscal nor monetary is effort which conducted in framework recovery economy national or could prevent happening crisis monetary which deep. The conclusion from this research is that the economy will recover in 2023 after the pandemic COVID-19 needs attention and must be resolved seriously and thoroughly with exists virus this could causing crisis in period long in field economy as well as health.